2011
DOI: 10.1371/journal.pone.0018531
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Cellular Effectors of Terrestrial Isopod Armadillidium vulgare: Meeting with Their Invaders, Wolbachia

Abstract: BackgroundMost of crustacean immune responses are well described for the aquatic forms whereas almost nothing is known for the isopods that evolved a terrestrial lifestyle. The latter are also infected at a high prevalence with Wolbachia, an endosymbiotic bacterium which affects the host immune system, possibly to improve its transmission. In contrast with insect models, the isopod Armadillidium vulgare is known to harbor Wolbachia inside the haemocytes.Methodology/Principal FindingsIn A. vulgare we characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 57 publications
3
51
0
Order By: Relevance
“…In A. vulgare , it has recently been shown that Wolbachia impact immune cellular processes [10,11,65]. We show here that Wolbachia symbiosis leads to a down-regulation of some A. vulgare immune genes.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In A. vulgare , it has recently been shown that Wolbachia impact immune cellular processes [10,11,65]. We show here that Wolbachia symbiosis leads to a down-regulation of some A. vulgare immune genes.…”
Section: Discussionsupporting
confidence: 55%
“…In A. vulgare , Wolbachia colonize not only the ovaries but also other tissues, particularly the immune cells [65,84]. Therefore, perturbation of the host immune gene expression could be a direct effect of the bacteria on immunity.…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescence in situ Hybridization was performed according to Chevalier et al [46] on a total of 4 µL for each pool fixed with 1% paraformaldehyde-PBS solution (137 mM NaCl, 8 mM Na 2 HPO 4 , 12H 2 O, 1.5 mM KH 2 PO 4 , 3 mM KCl, pH 7.3), at 35% formamide with the probes W1-Cy3 (5′-AATCCGGCCGARCCGACCC-3′) and W2-Cy3 (5′-CTTCTGTGAGTACCGTCATTATC-3′) (30 ng.mL −1 each) targeting Wolbachia 16S rRNA [47]. As in Chevalier et al [46] the samples were further stained with FITC-phalloidin (20 ng, Sigma) mixed into the hybridization buffer and with DAPI (Sigma) mixed into the mounting medium (AF1 antifading, Citifluor, England, 2.5 mg.mL −1 ). Detection was performed with an epifluorescent microscope (Axio Observer-A1, Zeiss) with Apotome (structured illumination) equipped with a 63X/1.25 objective (oil immersion) and with the AxioVision 4.8.1 software (Zeiss).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies on diverse insect-microbe symbiotic associations have revealed that the host organisms regulate infection densities of their symbionts by means of phagocytosis, antimicrobial peptides, lysozymes, reactive oxygen species, etc. (39)(40)(41)(42). These innate immune mechanisms may also comprise host-related stress factors for the symbionts.…”
Section: Host Fitness Is Negatively Affected By Infection With Symbiontmentioning
confidence: 99%